2014
DOI: 10.1073/pnas.1321014111
|View full text |Cite
|
Sign up to set email alerts
|

In vivo radiation response of proneural glioma characterized by protective p53 transcriptional program and proneural-mesenchymal shift

Abstract: Significance Glioblastoma is one of the most radio-resistant tumors, and the mechanisms of radioresistance are intensely studied. Here, we use a mouse model of proneural glioma to evaluate in vivo radiation-induced gene expression regulation at both the translational and transcriptional levels. We found that p53 and E2F are major regulators of the in vivo radiation response, and that there is little contribution from translational regulation, in contrast to previous in vitro reports. We also found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
165
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(177 citation statements)
references
References 33 publications
12
165
0
Order By: Relevance
“…Second, the efficient metabolic inhibition of tumor growth triggered by the mesenchymal GLN High cells is of particular interest because it has been shown that this subtype is the most resistant to therapy (3,36). Furthermore, a recent study has shown that radiation promotes a molecular shift from the proneural to the mesenchymal subtype (40). In this .…”
Section: Discussionmentioning
confidence: 99%
“…Second, the efficient metabolic inhibition of tumor growth triggered by the mesenchymal GLN High cells is of particular interest because it has been shown that this subtype is the most resistant to therapy (3,36). Furthermore, a recent study has shown that radiation promotes a molecular shift from the proneural to the mesenchymal subtype (40). In this .…”
Section: Discussionmentioning
confidence: 99%
“…Those findings suggested that STAT3 activation is involved in glioma tumorigenesis and tumor aggressiveness. Furthermore, in vivo study of glioma molecular response to ionizing radiation showed a time-dependent increase in pSTAT3-Y705 expressing tumor cells in a spontaneous GBM model generated in mice (23).…”
Section: Concordant Studies Have Reported Signal Transducer and Activmentioning
confidence: 98%
“…Mouse GSCs can overcome the damage of repeated irradiation through gradual activation of IGF1R-dependent resistance pathways (55), and repeated chemoand radiotherapies render human GSCs more aggressive and enrich their stem cell features (63,140). GBM recurrence is also associated with a transition from glial to mesenchymal phenotype and is related to poor outcome (141,142). Autophagy is another player in adaptive radioresistance mechanisms in GSCs (117).…”
Section: Molecular Pathways Implicated In Therapeutic Resistance Of Rmentioning
confidence: 99%